A20 promotes liver regeneration by decreasing SOCS3 expression to enhance IL‐6/STAT3 proliferative signals. Issue 5 (5th April 2013) - da Silva, Cleide G.; Studer, Peter; Skroch, Marco; Mahiou, Jerome; Minussi, Darlan C.; Peterson, Clayton R.; Wilson, Suzhuei W.; Patel, Virendra I.; Ma, Averil; Csizmadia, Eva; Ferran, Christiane
Abstract: Liver regeneration is of major clinical importance in the setting of liver injury, resection, and transplantation. A20, a potent antiinflammatory and nuclear factor kappa B (NF‐κB) inhibitory protein, has established pro‐proliferative properties in hepatocytes, in part through decreasing expression of the cyclin dependent kinase inhibitor, p21. Both C‐terminal (7‐zinc fingers; 7Zn) and N‐terminal (Nter) domains of A20 were required to decrease p21 and inhibit NF‐κB. However, both independently increased hepatocyte proliferation, suggesting that additional mechanisms contributed to the pro‐proliferative function of A20 in hepatocytes. We ascribed one of A20′s pro‐proliferative mechanisms to increased and sustained interleukin (IL)‐6‐induced signal transducer and activator of transcription 3 (STAT3) phosphorylation, as a result of decreased hepatocyte expression of the negative regulator of IL‐6 signaling, suppressor of cytokine signaling 3 (SOCS3). This novel A20 function segregates with its 7Zn not Nter domain. Conversely, total and partial loss of A20 in hepatocytes increased SOCS3 expression, hampering IL‐6‐induced STAT3 phosphorylation. Following liver resection in mice pro‐proliferative targets downstream of IL‐6/STAT3 signaling were increased by A20 overexpression and decreased by A20 knockdown. In contrast, IL‐6/STAT3 proinflammatory targets were increased in A20‐deficient livers, and decreased or unchanged in A20 overexpressing livers. Upstream of SOCS3, levels of its microRNA regulator miR203 were significantly decreased in A20‐deficient livers. Conclusion: A20 enhances IL‐6/STAT3 pro‐proliferative signals in hepatocytes by down‐regulating SOCS3, likely through a miR203‐dependent manner. This finding together with A20 reducing the levels of the potent cell cycle brake p21 establishes its pro‐proliferative properties in hepatocytes and prompts the pursuit of A20‐based therapies to promote liver regeneration and repair. (HEPATOLOGY 2013)